Qualitative and quantitative analysis of the defensive profile in breast cancer women: A pilot study. Issue 1 (June 2019) - Di Giuseppe, Mariagrazia; Di Silvestre, Annarita; Lo Sterzo, Rosa; Hitchcott, Paul; Gemignani, Angelo; Conversano, Ciro
This study analyzed the defensive functioning and profile of nine breast cancer women and identifies the differences from other cancer patients (N0) in the way they deal with internal conflicts and stressful situations related to the illness. Patients were interviewed and evaluated using the Defense Mechanisms Rating Scale Q-sort. Mean differences analysis showed that breast cancer patients use more reaction formation, omnipotence, and rationalization and less idealization of others-image and autistic fantasy, compared with other-site cancer patients. From the qualitative analysis of the defensive profile, displacement and repression appeared among the most representative defense mechanisms of breast cancer patients.